Causal Model of Variables Affecting the Creativity of Undergraduate Students - Banjob Boonchan; Phadungchai Pupat; Boonchan Seesan (My University, 2017)
This research aims to select variables affecting the creativity of undergraduate students and to develop a causal model from the results. A total of 760 students participated in this study. The instruments used were the Torrance Tests of visual and written language and a questionnaire about the variables that influence creativity. Also a confirmatory factor analysis (CFA), mean and standard deviations, and a path analysis with the LISREL version 8.8 and SPSS program were used. The results show that administration, teaching, instructional climate, motivation, and personality are the variables that affect the creativity of the undergraduate students. The results from the CFA show an acceptable goodness-of-fit. The means of creativity and variables affecting creativity of the undergraduate students were at a medium and high level (between 2.98 to 3.05 and between 3.94 to 4.13), respectively. The goodness-of-fit of the causal model of the variables affecting the creativity of the undergraduate students was developed on the basis of the empirical data as well. The statistical results obtained were χ2 = 125.28, df = 104, p-value = 0.07622, GFI = 0.98, AGFI = 0.97 and RMSEA = 0.016, all of which are based on specified criteria.
Keywords: LISREL; Goodness of fit; Variables; Causal model; Creativity in Education and Neuroscience